A deniable death - Seymour, Gerald (Thomas Dunne Books, 2013)
Pulled from home country duty to carry out a covert mission to assassinate a roadside bomber in the Middle East, a talented surveillance operative engages in a painstaking process to save lives while working under a constant threat of disavowal.